Boosting Direct Oxidation of Methane with Molecular Oxygen at Low Temperature over Rh/ZSM‐5 Catalyst. Issue 8 (31st March 2023) - Yu, Xing; Mao, Jianing; Wu, Bo; Wei, Yao; Sun, Yuhan; Zhong, Liangshu
Abstract: As a clean fossil energy and chemical feedstock, development of breakthrough strategies for direct conversion of methane (CH4 ) into various chemicals under mild reaction conditions is highly desired. Herein, Rh/ZSM‐5 catalyst was reported to convert CH4 to oxygenates with molecular oxygen (O2 ) in the presence of CO at low temperature with promising catalytic performance. The oxygenates productivity reached as high as 5638.0 μmol gcat. −1  h −1 . Structure characterization confirmed the existence of highly dispersed Rh2 O3 nanoparticles with an average diameter of 2.4 nm in the Rh/ZSM‐5 catalyst. Based on control experiments and mechanism study, it was suggested that CO plays a pivotal role over the Rh/ZSM‐5 catalyst to boost direct oxidation of methane. CO participates in water‐gas‐shift reaction to produce in‐situ H species, which enables to form *OH, *OOH and H2 O2 active species by reacting with O2 . The as‐obtained *OH, *OOH and H2 O2 species will thus render high activity for methane oxidation. Abstract : Direct oxidation of methane : ZSM‐5 supported nanoparticles Rh2 O3 catalyst exhibited promising catalytic performance with high oxygenates productivity for direct oxidation of CH4 to oxygenates with O2 in the presence of CO. CO played a pivotal role in boosting methane activation. CO participated in the water‐gas‐shift process and in‐situ H species were generated. The in‐situ H species further reacted with O2 to form H2 O2, *OH, *OOH species, which facilitated the direct oxidation of CH4 to oxygenates.